If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 2r = 4r + -1 Reorder the terms: 9 + 2r = -1 + 4r Solving 9 + 2r = -1 + 4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4r' to each side of the equation. 9 + 2r + -4r = -1 + 4r + -4r Combine like terms: 2r + -4r = -2r 9 + -2r = -1 + 4r + -4r Combine like terms: 4r + -4r = 0 9 + -2r = -1 + 0 9 + -2r = -1 Add '-9' to each side of the equation. 9 + -9 + -2r = -1 + -9 Combine like terms: 9 + -9 = 0 0 + -2r = -1 + -9 -2r = -1 + -9 Combine like terms: -1 + -9 = -10 -2r = -10 Divide each side by '-2'. r = 5 Simplifying r = 5
| 18p=-16p+5(3p-19) | | 6m=-102 | | 5*tan(x)+3=0 | | 3(w-2)=15 | | 4x=5y-2 | | -4(-1-3k)+4=80 | | 300-25x=500-75x | | -2(8+2x)=20 | | 6x-4(x-4)=22 | | 11.5b=-10.9b+7(3.4b+8.2) | | 24n+24=24+24n | | 7x+30=4x+87 | | 5-5x=40+4x | | 2(x-9)+9=2x-9(x-9) | | 8x-22=2x+32 | | 4(m+3)+11=2(3m+6)+13 | | 7-6(2a+3)=42 | | -33(12x)+29(21x)=(73-73)+(-737+98) | | -4j+10=-5j | | -15+m=4 | | -3f=8+f | | 2(6b-3)=-78 | | 3(x+7)=-6x-33 | | -19j-20=-6j-15j+18 | | 18=-2x-7x | | -20=31+3x | | 6b-12b+4c+6d= | | 2(x-5)3x=20 | | x+5x-7x+3-x=48 | | 1-(3y+3)=-8 | | -5q-10=-6q | | 4q-3y=27 |